2021
DOI: 10.1159/000517180
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Obesity in Predicting the Clinical Outcomes of COVID-19

Abstract: <b><i>Introduction:</i></b> The aim of this was to describe the predictors of mortality related to COVID-19 infection and to evaluate the association between overweight, obesity, and clinical outcomes of COVID-19. <b><i>Methods:</i></b> We included the patients &#x3e;18 years of age, with at least one positive SARS-CoV-2 reverse transcriptase-polymerase chain reaction. Patients were grouped according to body mass index values as normal weight &#x3c;25 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…This result was consistent with Simonnet et al, Kalligeros et al, and Sahin et al study. 1,18,19 Abdominal obesity or central obesity is assessed by waist circumference. COVID-19 severity is also associated with abdominal adipose tissue distribution.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with Simonnet et al, Kalligeros et al, and Sahin et al study. 1,18,19 Abdominal obesity or central obesity is assessed by waist circumference. COVID-19 severity is also associated with abdominal adipose tissue distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In this single-center prospective study, patients with severe and moderate COVID-19 disease were found to have similar BMI values below 30 kg/m2. Sahin et al showed that obese patients with BMI ≥35 kg/m2 had higher lung involvement rates and required longer noninvasive mechanical ventilation than overweight patients [ 35 ]. While several studies evaluated the impact of obesity on COVID-19 morbidity and mortality, the clinical course of overweight patients and various degrees of obesity have not been involved in meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meningkatnya IMT atau obesitas merupakan salah satu masalah kesehatan yang harus menjadi perhatian khusus saat kondisi pandemi, karena kondisi tersebut dikaitkan dengan faktor risiko yang dapat mempengaruhi kondisi klinis yaitu memperparah kondisi hingga kematian pada pasien Corona Virus Disease (Covid-19) (Adimara, et al, 2021;Aqmarina, et al, 2021;Plourdei, et al, 2021;Sahin, et al, 2021). Obesitas dapat memengaruhi tingkat keparahan Covid-19 berdasarkan beberapa mekanisme termasuk ketidaknormalan ventilasi paru, peradangan kronis, gangguan sistem imun, disfungsi endotel, efek biologis lokal dari ektopik disposisi lemak dalam jaringan visceral dan koagulasi (Dana, et al, 2021).…”
Section: Kata Kunciunclassified